2013
DOI: 10.1371/journal.pone.0071787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Brief Outreach Educational Intervention on the Translation of Acute Poisoning Treatment Guidelines to Practice in Rural Sri Lankan Hospitals: A Cluster Randomized Controlled Trial

Abstract: BackgroundIn developing countries, including Sri Lanka, a high proportion of acute poisoning and other medical emergencies are initially treated in rural peripheral hospitals. Patients are then usually transferred to referral hospitals for further treatment. Guidelines are often used to promote better patient care in these emergencies. We conducted a cluster randomized controlled trial (ISRCTN73983810) which aimed to assess the effect of a brief educational outreach (‘academic detailing’) intervention to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Although there would be a cost of care for managing these patients at peripheral hospitals, the expense is likely to be significantly less. Lessons from Sri Lanka suggest that increased support to peripheral hospitals can alter their patterns of poisoned patient transfers .…”
Section: Discussionmentioning
confidence: 99%
“…Although there would be a cost of care for managing these patients at peripheral hospitals, the expense is likely to be significantly less. Lessons from Sri Lanka suggest that increased support to peripheral hospitals can alter their patterns of poisoned patient transfers .…”
Section: Discussionmentioning
confidence: 99%
“…The top 24 global EM articles for 2013 are listed in Table . The complete database of all 434 global EM articles for 2013, as well as full summaries and critical analyses of the top 24 global EM of articles of 2013, can be found in Data Supplements S1 and S2 (available as supporting information in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the evidence supporting the WHO recommendations has been derived from tertiary hospital data, and this study supports a reevaluation of the current antibiotic recommendations for community‐dwelling patients. Finally, a study from Sri Lanka demonstrated that a brief educational workshop increased adherence to emergency treatment guidelines for acute poisonings, when compared to distributing printed guidelines alone …”
Section: Discussionmentioning
confidence: 99%
“…Finally, in order to continue to advance EM training and the overall provision of emergency care, programs must include training in quality improvement (QI) and research, topics not traditionally taught in many medical and nursing schools in low-resource settings. To illustrate this point, less than half of the programs mention a component of QI and/or research, and only two of the manuscripts have a local first author [31,44]. Furthermore, in order to determine which methods of training are most effective, we must move beyond metrics regarding knowledge acquisition and attitude and eventually look to patient-, community-, and population-based outcomes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of the high-scoring manuscripts focus on seven specific content areas (ultrasound, trauma, pediatrics, pediatric trauma, neurological emergencies, toxicological emergencies). They span the years 2012-2018, are pub- lished in twelve journals, and highlight work in thirteen countries ( Table 2) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Eleven of the manuscripts discuss general EM programs.…”
Section: Overview Of High-scoring Manuscriptsmentioning
confidence: 99%